OPTIMALISASI PENERAPAN SISTEM APLIKASI E-PUSKESMAS: TINJAUAN TERHADAP PROSES DAN KEEFEKTIFAN DI PUSKESMAS TAJINAN KABUPATEN MALANG - Soraya, Soraya; Nindy Oktoriani, Ervita; Adhe S, Maulidya (Malang: Sekolah Tinggi Ilmu Administrasi Malang, 2024)
The development of digital technology in this modern era has resulted in a digital transformation, including in the realm of health services. This effort is strengthened by the Republic of Indonesia Ministry of Health Regulation Number 24 of 2022, which regulates legal certainty in the management andadministration of Electronic Medical Records (RME). This regulation must be implemented by all health service facilities no later than the end of 2023. This research aims to analyze the implementation of the EPuskesmas Application System at the Tajinan Health Center, Malang Regency. The method used in this research is descriptive qualitative. Data collection was carried out through observations and interviews with health workers using the HOT-Fit information system evaluation model, which includes Human, Organizational, Technology and Benefit aspects. The research results show that the E-Puskesmas application has a variety of menus and features that are considered very profitable and useful, able to help lighten the workload of health workers. Community health center management also supports the implementation of this application by providing adequate hardware. However, there are stillshortcomings, namely the absence of official Standard Operating Procedures (SOP) regarding the implementation of E-Puskesmas, as well as a lack of special training for officers to operate the application. The implications of these findings indicate the importance of preparing official SOPs and appropriatetraining to optimize the implementation of the E-Puskesmas Application System at the Tajinan Health Center, Malang Regency.